Identification of continuing professional development needs of primary school English teachers of Kuala Terengganu District - R. Muthusamy, Ramasamy (1998)
The study was carried out mainly to identify the perceived needs for continuing professional development of primary school English teachers of Kuala Terengganu District. It also sought to find out the relationship between selected variables and the perceived needs for continuing professional development. The data was collected using a questionnaire from 82 primary school English teachers of Kuala Terengganu district. The findings of the study indicated that majority of the respondents have high perceived needs for continuing professional development. The study also revealed that the respondents have perceived needs in all the six categories identified in the questionnaire which were (A) Knowledge, (B) Teaching Strategies, (C) Classroom-Based Skills, (D) Pastoral Care, (E) Student Management Skills and (F) Personal Development. It was found that there was a significant correlation between age and perceived needs for continuing professional development but it was low in nature. The study recommended that provision of professional development activities for primary school English teachers of Kuala Terengganu District should be based on a needs assessment and teachers should be allowed to choose in-service courses based on their own needs. The study has also suggested that further research should be conducted to obtain a more in-depth view of the perception of professional needs of English teachers through other research designs.